Slouching towards engagement: interactions between people using psychedelics naturalistically and their healthcare providers - Boehnke, Kevin F.; Cox, Kasey; Weston, Cody; Herberholz, Moss; Glynos, Nicolas; Kolbman, Nicholas; Fields, Christopher W.; Barron, Julie; Kruger, Daniel J. (Frontiers in Psychiatry, 2023)
Introduction There is substantial public interest in psychedelics as potential treatments for psychiatric conditions. However, most psychedelics are criminalized under federal law in the USA, so it is unclear whether use occurs with clinical support. Our objective was to assess whether naturalistic psychedelic use occurs with clinical support, interactions between those using psychedelics and healthcare providers (psychiatrist, therapist, or primary physicians), and use characteristics. Methods We conducted an online, anonymous, confidential, cross-sectional survey of adults reporting psychedelic use (N = 1221) through a psychedelics advocacy event and social media between 9/18/2022 and 11/5/2022. We assessed participant disclosure of psychedelic use with their psychiatric care provider (PsyCP) and/or primary care provider (PCP), desire for provider support, access to support, and rate of taking prescribed psychoactive medications alongside psychedelics. Results Among participants with such care providers, 22% disclosed psychedelic use to their PCP vs. 58% to their PsyCP. Participants were less confident in PCP vs. PsyCP ability to integrate psychedelics into treatment. Common reasons for nondisclosure included stigma, inadequate provider knowledge, and legal concerns. 23% reported taking psychedelics on the same day as potentially interacting psychiatric medications (e.g., anxiolytics, antidepressants). Despite 81% of participants desiring therapist support during psychedelic experiences, only 15% had received such support. Discussion Our results show that psychedelic use is generally disconnected from primary and psychiatric clinical care. This disconnection may result in safety issues, including inadequate screening for contraindicated conditions, lack of support during emergent adverse events, and drug interactions. Enhanced clinical education and orienting drug policy towards known harms and benefits of psychedelics is needed.